Factors Associated With Body Weight Status Among Children With Autism Spectrum Disorder In Kuching Devision, Sarawak - Teoh, Wan Jool (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Introduction: Unhealthy body weight status is a common problem among children with autism spectrum disorder (ASD) and can lead to substantial adverse health impacts. This cross-sectional study aimed to determine the assocfation between sociodemographic characteristics, parental feeding practices, child eating behaviour, dietary intakes with body weight status among ASD children in Kuching Division, Sarawak. Methodology: A total of 124 ASD children (83.9% boys and 16.1% girls) aged 2-11 years with their caregivers from 15 special child care centres within Kuching division were recruited via universal sampling, anthropometric measurements were taken for each child and Body Mass Index-for-age z-score were computed using Anthroplus software version 1.0.4. Interviewer-administrated questionnaires comprised of sociodemographic information, Child Feeding Questionnaire, Child Eating Behaviour Questionnaire, and one-day 24-hour dietary recalls were used. Data were analysed using IBM SPSS version 22. Results: The prevalence of risk of overweight, overweight, obese and underweight among the children were 4.8% (2.9% boys; 15.0% girls), 16.9% (17.3% boys; 15.0% girls), 20.2% (23.1 % boys; 5.0 % girls) and 3.2% (3.8% boys; 0% girls) respectively. The logistic regression revealed that caregivers with high perceived child weight (AOR 31.388, 95% CI= 5.363-183.708), high concern child weight (AOR 1.774, 95% CI= 1.112-2.829) and sodium intakes (AOR 3.747, 95% CI= 1.515-9.269) were significantly associated with increased risk of overweight or obesity. Conclusion: High prevalence of overweight and obesity among the ASD children was observed in the current study. Caregivers should be the pre-eminent target for education concerning healthy feeding practices and nutrition to ameliorate weight status. The involvement of caregivers in the interventional programmes is crucial especially those with high in perceived child weight and concern child weight to curb overweight or obesity among children with ASD.